LIU XING’S AMBITION TO BE A SCIENTIST IN CHEN SHI-ZHENG’S DARK MATTER (2008) MOVIE: A PSYCHOANALYTIC APPROACH - KUSUMA., ADNAN (2010)
The major problem of this study is how ambition is reflected in the major character’s personality. The aim of this study is to analyze Chen Shi- Zheng’s Dark Matter based on the structural elements and the development of personality of the major character based on Psychoanalytic Approach. This study focuses on the major character, namely Liu Xing. The benefit of this study is to give additional information which can be used by the other literature researchers who are interested in analyzing this play. This study uses two data sources, namely primary and secondary data source. The primary data source is the movie of Dark Matter, while the secondary data are taken from some information needed. The method of data collection is qualitative method. The analysis is started by analyzing Liu Xing’s id, ego, and superego. For the last, the writer makes an analysis of Liu Xing’s character using defense mechanism. Based on the analysis, the writer can draw the following conclusions. Firstly, the structural elements of the movie present unity. Chen Shi-Zheng takes the character with particular characterization. The plot of this story can be categorized into traditional plot that consists of the rise of complication, climax and resolution. Dark Matter movie begins with the exposition followed by conflict and climax, and ended by resolution. Secondly, based on psychoanalytic approach to analyze the data of the research. Dark Matter movie is a very interesting movie to be studied, which is manifested in his psychoanalytic analysis of its character. The major factors of the movie are the human ambition and human frustration. The movie shows the conflict among them it and how superego obeys the id and how the ego becomes a scientist.